Integrated physiological and comparative proteomics analysis of contrasting genotypes of pearl millet reveals underlying salt‐responsive mechanisms. Issue 1 (13th December 2021) - Jha, Shweta; Maity, Sudipa; Singh, Jawahar; Chouhan, Chaya; Tak, Nisha; Ambatipudi, Kiran
Abstract: Salinity stress poses a significant risk to plant development and agricultural yield. Therefore, elucidation of stress‐response mechanisms has become essential to identify salt‐tolerance genes in plants. In the present study, two genotypes of pearl millet ( Pennisetum glaucum L.) with contrasting tolerance for salinity exhibited differential morpho‐physiological and proteomic responses under 150 mM NaCl. The genotype IC 325825 was shown to withstand the stress better than IP 17224. The salt‐tolerance potential of IC 325825 was associated with its ability to maintain intracellular osmotic, ionic, and redox homeostasis and membrane integrity under stress. The IC 325825 genotype exhibited a higher abundance of C4 photosynthesis enzymes, efficient enzymatic and non‐enzymatic antioxidant system, and lower Na + /K + ratio compared with IP 17224. Comparative proteomics analysis revealed greater metabolic perturbation in IP 17224 under salinity, in contrast to IC 325825 that harbored pro‐active stress‐responsive machinery, allowing its survival and better adaptability under salt stress. The differentially abundant proteins were in silico characterized for their functions, subcellular‐localization, associated pathways, and protein–protein interaction. These proteins were mainly involved in photosynthesis/response to light stimulus, carbohydrate and energy metabolism, and stress responses. Proteomics data were validated through expression profiling of the selected genes, revealing a poor correlation between protein abundance and their relative transcript levels. This study has provided novel insights into salt adaptive mechanisms in P. glaucum, demonstrating the power of proteomics‐based approaches. The critical proteins identified in the present study could be further explored as potential objects for engineering stress tolerance in salt‐sensitive major crops.